Developing Flashcards Learning Media to Teach Grammar in Recount Texts for Tenth Grade - Oryzanda Oryzanda; Ahmad Saifudin; Widiarini Widiarini (Universitas Pendidikan Mandalika, 2022)
Language plays a crucial part in the foundation of communication in daily life and academic activity. Learning an additional language such as English in school is very important. Mastery of English grammar is required to compose a word or sentence in English. It takes grammar proficiency to create words or phrases in English. Students in class X IIK 2 MA Bustanul Muta'allimin comprise the study's sample population. Most of the students in this class had trouble putting simple sentences together. According to the results of the needs analysis, the result of the questionnaires, 77% of the students had difficulties constructing their simple sentences in English. Furthermore, 80% of the 13 samples indicated they wished to learn using engaging media. This research was conducted aiming to develop learning media in teaching grammar. The ADDIE model design, created by Dick and Carry in 1996, is used in this research process, known as research and development (R&D). There are five steps in this development that are following the ADDIE model, that is Analysis, Design, Development, Implementation, and Evaluation. The result of media expert validation and material expert validation achieved scores of 80.26% and 68.05%, respectively. A score of 76% was obtained when the questionnaire about using learning media was completed by student respondents. Flashcard media have a level of validity that makes them appropriate for usage, according to the result of expert validation and student response. As a result, this learning media is used effective tool for increasing students' interest in studying.